Factors Affecting Investment: Case in Central Java - Muhammad Ruswensa Maha Putra; Nur Hidayah (IECON: International Economics and Business Conference, 2023)
This study aims to analyze the factors that influence domestic investment. This research is a quantitative study conducted to determine the direction and magnitude of the influence of the Human Development Index (HDI), District Minimum Wage, Gross Regional Domestic Product (GRDP), Workforce, and Taxes on PMDN in regencies/cities in Central Java province in 2019- 2021. The data used is a combination of time series and cross section data obtained from BPS Central Java. The analysis tool used is panel data regression. The selected model is the FEM model. Based on the results of the analysis that has been done, it can be concluded that there are two variables that have a positive and significant effect on PMDN in the model, namely GRDP and UMK. Meanwhile, the other three variableshave no significant effect on PMDN. Based on research that has been done to keep the investment climate stable, the government can increase the minimum wage and maintain economic stability.